Respuesta :

This is actually really nice to solve with substitution, since the second equation is already solved in terms of y. So what you do is take everything on the right of the second equation, and substitute it into the first wherever you see a y. This results in the equation 
[tex]4x + 9(-\frac13x + 2) = 24[/tex].
Now it is a matter of distributing the 9, and adding applicable things. 
[tex]4x - 3x + 18 = 24[/tex]
[tex]x = 6[/tex]
Substitute this value for x back into either of the original equations to get the equation. 
[tex]y = -\frac13(6) + 2[/tex]
[tex]y = 0[/tex]

So x = 6, y = 0 is the solution to the equation.

Note: You can check this by substituting these values into both equations to ensure you have valid values.